The Copy Number Variation of OsMTD1 Regulates Rice Plant Architecture - Liu, Qing; Xu, Jinke; Zhu, Yunhua; Mo, Yuxing; Yao, Xue-Feng; Wang, Ruozhong; Ku, Wenzhen; Huang, Zhigang; Xia, Shitou; Tong, Jianhua; Huang, Chao; Su, Yi; et al. (Frontiers in Plant Science, 2021)
Copy number variation (CNV) may have phenotypic effects by altering the expression level of the gene(s) or regulatory element(s) contained. In the genome of a rice cultivar (Oryza sativa ssp. japonica cv. Nipponbare), we surprisingly found a locus Loc_Os08g34249 identical in DNA sequence to OsMTD1, a gene regulates tillering in rice. We further confirmed that the OsMTD1 located region involved a CNV (OsMTD1-located CNV), and Loc_Os08g34249 is derived from a 13,002-bp tandem duplication in the nearby region of OsMTD1, implying the OsMTD1 and Loc_Os08g34249 are reciprocal tandem duplication of the 13,002-bp segment. Further survey of 230 rice cultivars showed that the duplication only occurred in several japonica rice cultivars. Based on local alignments showing OsMTD1 and pri-miR156f as the main functional components in this segment, a CNV overlapping OsMTD1 and pri-miR156f was identified. Phylogenetic tree or evolution analysis showed that the CNV fragment had distant evolutionary relationships among different rice cultivars, suggesting that the CNV fragment might have important function in rice. In this work, we attempted to provide a direct link between this CNV and rice phenotypes. The cause-and-effect survey between the CNV and particular phenotypes in different rice cultivars indicated that this CNV region contributed to compact plant architecture. It was found that this CNV not only directly influences rice tiller number and leaf angle, but also regulates pri-miR156f transcription. Further transgenic approaches verified that this CNV regulates phenotypes through the dosage and position effects on OsMTD1 and pri-miR156f. Thus, this work identified a CNV containing a protein-coding gene OsMTD1 and a regulatory element osa-miR156f, and further provided a putative molecular explanation for the connection between this CNV and a particular phenotype.